(untitled) (Biocenosis, 2023)
Environmental pollution with antibiotics and the spread of resistant bacteria may cause health damage, the emergence of new pandemics, the disruption of the balance of ecosystems, food insecurity, and a global economic crisis. Given this context, this article broaches a documentary analysis of the causes and consequences of the problem, with the main objective of proposing measures to reduce risks. As a result of the research, access to this problem is proposed from the “One world, one health” approach, where it is crucial to implement good practices for the prevention of infectious diseases and the optimal use of antibiotics in human, animal, and plant health. This must be accompanied by research processes, social awareness, citizen participation, political incidence and management that allow the preservation of a healthy and ecologically balanced environment.